2013
DOI: 10.1016/j.jrurstud.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Arranging public support to unfold collaborative modes of governance in rural areas

Abstract: Raising collective agency is key to successful place-based development approaches. Existing policy arrangements have, however, been criticised, suggesting a need to effectuate more collaborative modes of governance. This paper shall contribute to a better understanding of how public support can best be arranged to raise collective agency for a more collaborative mode of governance in rural areas. The paper elaborates on findings of empirical investigations conducted within the EU FP7 project DERREG. It will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 54 publications
0
55
0
8
Order By: Relevance
“…In that way, IPs can provide a space where expectations and tensions related to transition processes, approaches to innovation, and the new roles and tasks for different stakeholders (including for research and researchers) can be discussed and negotiated [12]. This joint reconsideration and restructuring has been found essential for collective action and agricultural innovation [13]. To support such reflection, more documentation that is rigorous and analysis of IP processes are needed, using systematic approaches as [14] have done for participatory research.…”
Section: Figmentioning
confidence: 99%
“…In that way, IPs can provide a space where expectations and tensions related to transition processes, approaches to innovation, and the new roles and tasks for different stakeholders (including for research and researchers) can be discussed and negotiated [12]. This joint reconsideration and restructuring has been found essential for collective action and agricultural innovation [13]. To support such reflection, more documentation that is rigorous and analysis of IP processes are needed, using systematic approaches as [14] have done for participatory research.…”
Section: Figmentioning
confidence: 99%
“…In this section, the potentials of the integrated, analytical framework on rural regional learning will be briefly illustrated with preliminary findings from the Westerkwartier case study area, as part of ongoing research (Roep et al 2011, Wellbrock et al 2011a). The Westerkwartier is a predominantly rural area in the province of Groningen in the North of The Netherlands (see figure 5).…”
Section: Preliminary Findings From the Westerkwartier Netherlandsmentioning
confidence: 99%
“…Finally, in the Westerkwartier, as well as in other DERREG case study regions, it has been shown that grassroots development initiatives can cover a wide range of development aspects, such as nature, landscape & environment, civic & community development, SME support and culture & history. To a lesser extent, the inventoried initiatives also deal with (multifunctional) agriculture, agriculture & forestry, tourism, and education, training & employment (Wellbrock et al 2011a). All of these contribute to place-based development in the Westerkwartier and need to get involved in an integrated, place-based development vision for the region.…”
Section: Ad1) Mapping Of Supporting Policies Actors and Available Knmentioning
confidence: 99%
See 2 more Smart Citations